Screening for depression and anxiety among patients with acute coronary syndrome in acute care settings: a scoping review. Issue 9 (9th September 2020) - Marin, Tania S.; Walsh, Sandra; May, Nikki; Jones, Martin; Gray, Richard; Muir-Cochrane, Eimear; Clark, Robyn A.
ABSTRACT: Objective: The aim of this review was to scope the literature for publications on the practice of screening for depression and anxiety in acute coronary syndrome patients in acute care by identifying instruments for the screening of anxiety and/or depression; determining if screening for anxiety and/or depression has been integrated into cardiac models of care and clinical pathways; and identifying any evidence practice gap in the screening and management of anxiety and/or depression in this population. Introduction: Depression in acute coronary syndrome is bidirectional. Depression is an independent risk factor for cardiovascular disease, and comorbid depression is associated with a twofold greater risk of mortality in patients with cardiovascular disease. The presence of acute coronary syndrome increases the risk of depressive disorders or anxiety during the first one to two years following an acute event, and both depression and anxiety are associated with a higher risk of further acute coronary health concerns. Clinical practice guidelines have previously recommended routine screening for depression following a cardiac event, although many current guidelines do not include recommendations for screening in an acute setting. To date there have been no previous scoping reviews investigating depression and anxiety screening in patients with acute coronary syndrome in the acute care setting. Inclusion criteria: Adults (18 years and over) with acute coronary syndrome who are screened for anxiety and/or depression (not anxiety alone) in an acute care setting. Methods: A systematic search of the literature was conducted by a research librarian. Research studies of any design published in English from January 1, 2012, to May 31, 2018, were included. Data were extracted from the included studies to address the three objectives. Purposefully designed tables were used to collate information and present findings. Data are also presented as figures and by narrative synthesis. Results: Fifty-one articles met the inclusion criteria. Primary research studies were from 21 countries and included 21, 790 participants; clinical practice guidelines were from two countries. The most common instruments used for the screening of depression and anxiety were: i) the Hospital Anxiety and Depression Scale (n = 18); ii) the Beck Depression Inventory (n = 16); and iii) the nine-item Patient Health Questionnaire (n = 7). Eleven studies included screening for anxiety in 2181 participants (30% female) using the full version of the Hospital Anxiety and Depression Scale. The State-Trait Anxiety Inventory was used to screen 444 participants in three of the studies. Four studies applied an intervention for those found to have depression, including two randomized controlled trials with interventions targeting depression. Of the seven acute coronary syndrome international guidelines published since 2012, three (43%) did not contain any recommendations for screening for depression and anxiety, although four (57%) had recommendations for treatment of comorbidities. Conclusions: This review has identified a lack of consistency in how depression and anxiety screening tools are integrated into cardiac models of care and clinical pathways. Guidelines for acute coronary syndrome are not consistent in their recommendations for screening for depression and/or anxiety, or in identifying the best screening tools.